Penerapan Pembelajaran CO-OP CO-OP dengan Menggunakan Media Wingeom untuk Meningkatkan Penalaran Pembelajaran Siswa MI Tarbiyatul Huda - Intan Nadiroh (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2016)
Today the progress of science and technology requires a person can master the information and knowledge. Thus required an ability to obtain, select and process information. These abilities require critical thinking, systematic, logical and creative. Therefore we need an education program to develop the ability to think critically, systematic, logical and creative. One program that is necessary for it is mathematics. Mathematics is a subject that fosters students to think logically. This study aims to find and analyze the extent Application of Learning CO-OP CO-OP Using the Media to Enhance Reasoning students Wingeom MI Tarbiyatul Huda